Comparative Ser/Thr/Tyr phosphoproteomics between two mycobacterial species: the fast growing Mycobacterium smegmatis and the slow growing Mycobacterium bovis BCG - Nakedi, Kehilwe C.; Nel, Andrew J. M.; Garnett, Shaun; Blackburn, Jonathan M.; Soares, Nelson C. (Frontiers in Microbiology, 2015)
Ser/Thr/Tyr protein phosphorylation plays a critical role in regulating mycobacterial growth and development. Understanding the mechanistic link between protein phosphorylation signaling network and mycobacterial growth rate requires a global view of the phosphorylation events taking place at a given time under defined conditions. In the present study we employed a phosphopeptide enrichment and high throughput mass spectrometry-based strategy to investigate and qualitatively compare the phosphoproteome of two mycobacterial model organisms: the fast growing Mycobacterium smegmatis and the slow growing Mycobacterium bovis BCG. Cells were harvested during exponential phase and our analysis detected a total of 185 phospho-sites in M. smegmatis, of which 106 were confidently localized (localization probability (LP) =0.75; PEP=0.01). By contrast, in M. bovis BCG the phosphoproteome comprised 442 phospho-sites, of which 289 were confidently localized. The percentage distribution of Ser/Thr/Tyr phosphorylation was 39.47, 57.02 and 3.51 % for M. smegmatis and 35, 61.6 and 3.1% for M. bovis BCG. Moreover, our study identified a number of conserved Ser/Thr phosphorylated sites and conserved Tyr phosphorylated sites across different mycobacterial species. Overall a qualitative comparison of the fast and slow growing mycobacteria suggests that the phosphoproteome of M. smegmatis is a simpler version of that of M. bovis BCG. In particular, M. bovis BCG exponential cells exhibited a much more complex and sophisticated protein phosphorylation network regulating important cellular cycle events such as cell wall biosynthesis, elongation, cell division including immediately response to stress. The differences in the two phosphoproteomes are discussed in light of different mycobacterial growth rates.